Productivity of Cuba OM-22 grass under different planting densities and harvest frequencies - Vargas Rojas, Jorge Claudio (2023)
Three planting densities, defined by the distances between rows, which were: 70 cm (4375 kg biomass ha-1), 85 cm (3750 kg biomass ha-1) and 100 cm (3125 kg biomass ha-1) and two harvest frequencies, at 45 and 70 days after the uniform cutting grass (auc) were evaluated. The experiment was carried out between December 2020 and May 2021 at the Santa Cruz Experimental Farm of the University of Costa Rica. A strip design was used, where the production of fresh and dry biomass, plant height, stem and leaf length, chlorophyll content, crude protein, and number of nodes per stem were quantified; an analysis of variance was performed for each variable. The use of a planting distance of 70 cm with a harvest frequency of 70 auc, showed higher values ​​for fresh biomass (p < 0,0001), dry biomass production (p < 0,0068), height (p < 0,0194) and stem length (p < 0,0093), compared to the other combinations. While a combination of a planting distance of 85 cm and a harvest frequency of 45 auc, presented higher values ​​for chlorophyll content (p < 0,0284) and percentage of crude protein (p < 0,0134). At early cutting ages there was higher biomass production, while at later ages there was a higher content of chlorophyll and crude protein. Due to productivity and protein content, Cuba OM-22 is an alternative for forage banks.